2022
DOI: 10.1088/1741-2552/ac9258
|View full text |Cite
|
Sign up to set email alerts
|

Stable, long-term single-neuronal recording from the rat spinal cord with flexible carbon nanotube fiber electrodes

Abstract: Objective. Flexible implantable electrodes enable months-long stable recording of single-unit signals from rat brains. Despite extensive efforts in the development of flexible probes for brain recording, thus far there are no conclusions on their application in long-term single neuronal recording from the spinal cord which is more mechanically active. To this end, we realized the chronic recording of single-unit signals from the spinal cord of freely-moving rats using flexible carbon nanotube fiber (CNTF) elec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 62 publications
(81 reference statements)
0
4
0
Order By: Relevance
“…Simultaneously, there was no evident alteration in the structure and no signal degradation at the stimulation sites after implantation for 6 weeks, implying excellent chronic biocompatibility and stability. Liu et al [139] applied flexible CNTF electrode on intraspinal recording of freely-moving rats, demonstrating that CNTF microelectrodes greatly reduced the gliosis compared to the stiff metal electrodes and that single-unit signals could be recorded continuously without electrode repositioning for 3-4 months by increasing the insulation thickness. The bending stiffness per width was ≈4.2 × 10 3 nN m, much smaller than silicon probes (4.6 × 10 5 nN m), but still higher than those of neural tissues (<1 nN m).…”
Section: Fibrous Carbon Materialsmentioning
confidence: 99%
“…Simultaneously, there was no evident alteration in the structure and no signal degradation at the stimulation sites after implantation for 6 weeks, implying excellent chronic biocompatibility and stability. Liu et al [139] applied flexible CNTF electrode on intraspinal recording of freely-moving rats, demonstrating that CNTF microelectrodes greatly reduced the gliosis compared to the stiff metal electrodes and that single-unit signals could be recorded continuously without electrode repositioning for 3-4 months by increasing the insulation thickness. The bending stiffness per width was ≈4.2 × 10 3 nN m, much smaller than silicon probes (4.6 × 10 5 nN m), but still higher than those of neural tissues (<1 nN m).…”
Section: Fibrous Carbon Materialsmentioning
confidence: 99%
“…Alternatives to metal microwires have been explored, most notably carbon fiber microelectrodes (figure 1(B)). While similar in elastic modulus to some metals, carbon fiber electrodes deform more elastically than metal microwires, and are capable of returning to their original shape after thousands of cycles of deformation without significant material fatigue [93], an advantageous property in more mobile implant locations such as the spinal cord, which can experience up to 10%-20% tensile strain during normal movement [94]. Carbon fiber electrodes have also demonstrated relatively enhanced durability, conductivity, and resistance to corrosion [95,96], making them a promising material for the continued development of devices in the microwire family.…”
Section: Microwiresmentioning
confidence: 99%
“…Median lifespans for rigid and flexible substrates were found to be 216 and 108.5 d respectively. Ninety seven studies were included in the analysis, for which the supporting data can be found in supplementary data table 2 [12,17,30,90,94,96,97,101,114,115,121,131,136,142,153,168,170,223,241,242,244,331,379,389,390,393,394,.…”
Section: Comparison Of In Vivo Lifespan By Device Characteristicsmentioning
confidence: 99%
“… 17 20 As a result, electrophysiological recordings in the spinal cord are mostly restricted to ex vivo , 21 , 22 anesthetized, 23 26 or acute preparations. 27 Even in the impressive but few examples of spinal recordings in awake-behaving contexts, animals were highly constrained, 28 33 motor activity was tightly circumscribed (e.g., isometric contractions of wrist muscles), 28 , 29 , 31 , 32 and/or neurons were recorded one at a time 30 , 34 , 35 or for short time periods. 30 , 34 Importantly, because the spinal cord mediates whole-body motor behaviors, a deeper understanding of spinal circuits requires unrestrained recording during precisely those actions that drive the most severe displacements of tissue.…”
Section: Introductionmentioning
confidence: 99%